Intrahepatic Sampling for the Elucidation of Antiviral Clinical Pharmacology. Issue 2 (March 2017) - Venuto, Charles S.; Talal, Andrew H.
Abstract: Although the importance of the liver in clinical pharmacology is widely recognized, little is known in humans concerning its function in vivo at the hepatocyte level and how pharmacological functions are altered in the setting of advanced liver disease. Several recent proof‐of‐principle studies with first‐generation DAAs have demonstrated the feasibility of serial liver sampling for pharmacological studies. These studies have begun to describe the liver‐to‐plasma concentration ratio and how this ratio is altered in the setting of advanced liver disease. These data are particularly relevant to individuals with substance‐use disorders because many have advanced liver disease as a consequence of long‐standing viral hepatitis infection or continued use of hepatotoxins such as alcohol. Future research should attempt to develop standardized and reproducible methods to assess liver drug concentration, complex drug interactions, and pharmacogenomics in humans to permit elucidation of the clinical pharmacology within the liver.